1971
DOI: 10.1192/bjp.118.547.683
|View full text |Cite
|
Sign up to set email alerts
|

Phobic Disorders Four Years after Treatment: A Prospective Follow-up

Abstract: In recent years several workers have followed-up the status of patients with phobic disorders after treatment (Terhune, 1949; Friedman, 1950; Tucker, 1956; Roberts, 1964; Sim and Houghton, 1966; Marks and Gelder, 1965; Marks, Birley and Gelder, 1966). These studies were retrospective in that evaluation was largely based on past records, and systematic interviews did not provide the main source of data. Some patients were included with phobias of duration ranging from three days to 32 years, while follow-up res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

1973
1973
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(27 citation statements)
references
References 12 publications
1
24
0
2
Order By: Relevance
“…Ten patients had remained symptom free for over two years and twenty-one patients for over one year. This shows that the improvement was maintained following treatment confirming the findings of other studies on the long-term effects of behaviour therapy [ 15, [34][35][36] and behavioural instruction [ 151.…”
Section: Discussionsupporting
confidence: 93%
“…Ten patients had remained symptom free for over two years and twenty-one patients for over one year. This shows that the improvement was maintained following treatment confirming the findings of other studies on the long-term effects of behaviour therapy [ 15, [34][35][36] and behavioural instruction [ 151.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is similar to the results of de Beurs and co-workers (1995) (41%) and Ö st and Jansson (1993) (46-50%). Thus, exposure outcome seems to be much more effective in terms of remission than earlier publications indicated (Emmelkamp & Kuipers, 1979;Lelliott et al, 1987;Marks, 1971;McPherson et al, 1980).…”
Section: Discussionmentioning
confidence: 71%
“…There is even less data about complete remission after exposure. Some authors (Lelliott, Marks, Monteiro, Tsakiris, & Noshirvani, 1987;Marks, 1971;McPherson, Brougham, & McLaren, 1980) reported that only 5-20% were free from agoraphobic symptoms at follow-up (FU) but remission criteria lacked in appropriate operationalization. Two studies compared symptom levels of agoraphobics after exposure with data of healthy controls (de Beurs, Lange, van Dyck, & Koele, 1995;Fava, Rafanelli, Ottilini, et al, 2001;Ö st, Westling, & Hellstrom, 1993), reporting a much higher percentage (41-46%) of patients with complete remission phobic anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The phobic images are only visualized for a few seconds at a time, and the subject is asked to relax between images. Figure 1. shows results in phobic disorders treated in an early series of trials by Gelder and myself (Marks, 1971). Desensitization in fantasy reduced phobias more than a comparison group which had dynamic psychotherapy.…”
Section: Results Of Exposure In Phobic and Obsessive-compulsive Disormentioning
confidence: 88%